IFNAR2 relevance in the clinical outcome of individuals with severe COVID-19 - Fricke-Galindo, Ingrid; Martínez-Morales, Alfonso; Chávez-Galán, Leslie; Ocaña-Guzmán, Ranferi; Buendía-Roldán, Ivette; Pérez-Rubio, Gloria; Hernández-Zenteno, Rafael de Jesus; Verónica-Aguilar, Abigail; Alarcón-Dionet, Aimé; Aguilar-Duran, Hiram; Gutiérrez-Pérez, Ilse Adriana; Zaragoza-García, Oscar; et al. (Frontiers in Immunology, 2022)
Interferons (IFNs) are a group of cytokines with antiviral, antiproliferative, antiangiogenic, and immunomodulatory activities. Type I IFNs amplify and propagate the antiviral response by interacting with their receptors, IFNAR1 and IFNAR2. In COVID-19, the IFNAR2 (interferon alpha and beta receptor subunit 2) gene has been associated with the severity of the disease, but the soluble receptor (sIFNAR2) levels have not been investigated. We aimed to evaluate the association of IFNAR2 variants (rs2236757, rs1051393, rs3153, rs2834158, and rs2229207) with COVID-19 mortality and to assess if there was a relation between the genetic variants and/or the clinical outcome, with the levels of sIFNAR2 in plasma samples from hospitalized individuals with severe COVID-19. We included 1,202 subjects with severe COVID-19. The genetic variants were determined by employing Taqman® assays. The levels of sIFNAR2 were determined with ELISA in plasma samples from a subgroup of 351 individuals. The rs2236757, rs3153, rs1051393, and rs2834158 variants were associated with mortality risk among patients with severe COVID-19. Higher levels of sIFNAR2 were observed in survivors of COVID-19 compared to the group of non-survivors, which was not related to the studied IFNAR2 genetic variants. IFNAR2, both gene, and soluble protein, are relevant in the clinical outcome of patients hospitalized with severe COVID-19.